On some discretization of Yang-Mills equations in Minkowski space - Sushch, V. (Нелинейные граничные задачи, 2003)
Using methods of differential geometry, a discrete analog of the Yang-Mills equations in Minkowski space is constructed. The gauge transformation law in a discrete formulation is given and gauge invariance of discrete Yang-Mills equations is studied.